Teknologi ﻿Edible Coating ﻿﻿Menggunakan Lilin Lebah (﻿Beeswax) ﻿Dan Kitosan Terhadap Mutu Buah Jambu Kristal (﻿Psidium guajava ﻿L. VAR. KRISTAL) - Naritha Yolanda; Noor Khamidah; Akhmad Rizali (Agroekotek View, 2021)
This study aims to determine the effect of beeswax and chitosan on the quality of crystal guava fruit (Psidium guajava L. Var. Crystals) and to determine the proper formulation of beeswax and chitosan on the quality of crystal guava fruit (Psidium). guajava L. Var. Crystals). This research was conducted at the Integrated Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University from July to September 2020. This study used a completely randomized design (CRD) with one factor, namely without coating or control (P0), 4% beeswax (P1), chitosan 2. , 5% (P2) and combination (P3). Observation benchmarks are weight loss, fruit texture, fruit color, fruit taste, and fruit aroma. Crystal guava fruit used in this study is a light green ripe guava fruit that has been harvested and taken to the Integrated Laboratory of the Agroecotechnology Department for the application of coating materials with three types of treatment and one control or without treatment and stored for four weeks at room temperature with observation parameters. quality in the form of weight loss data and organoleptic test data in the form of color, texture, and fruit taste. Weight loss data and organoleptic test data were analyzed using the De-Garmo method to determine the best treatment.The results showed that the edible coating technology had a very significant effect on the storage of crystal guava fruit based on the quality parameters of fruit weight, fruit texture, fruit color, fruit taste and fruit aroma indicating that beeswax treatment was the best treatment. Based on the calculation of the De-Garmo method, the correct formulation for the quality of crystal guava fruit is the 4% beeswax treatment with the best calculation results on days 7 to 14 with a total product value of 36.8.Copyright ( 2020Agroekotek View. All rights reserved.